Hom and Honiara: Interpreting, importing, and adapting "home" in Solomon Islands. (11th August 2022) - Maggio, Rodolfo
Abstract: The residents of Gilbert Camp, an illegal settlement on the outskirts of Honiara, the capital city of Solomon Islands, recurrently declare that life in town is hard. However, they have been migrating there, they keep doing so notwithstanding great challenges, and create the conditions for others to settle too. The apparent contradiction between their ideas and behaviours is resolved by looking at their home‐making practices, and interpreting negative statements as commentaries. These commentaries evaluate their efforts to turn Honiara into a home and a place where they can live the "good" life. Home is not just a matter of urban belonging and place‐making, neither it is just a matter of surviving in the "hard" urban context; rather it is a complex negotiation between cultural priorities, the specific needs of local communities, and their commitment to create a home away from home.